New oral cytodiagnostic criteria predict change to oral epithelial dysplasia (OED) and cancerization. Issue 3 (23rd January 2021) - Suzuki, Taiki; Isaka, Eisaku; Hiraga, Chiho; Akiyama, Yurie; Okamura, Masahiro; Oomura, Yusuke; Hashimoto, Kazuhiko; Sato, Kazumichi; Tanaka, Yoichi; Nomura, Takeshi
Abstract: Objectives: The purpose of this retrospective observational study was to evaluate the specificity of the new oral cytodiagnostic criteria and whether the new criteria predict change to oral epithelial dysplasia (OED) and cancerization for leukoplakia and oral lichen planus (OLP). Study design: Fifty‐three cases of leukoplakia without OED and 126 cases of OLP were included in this study. Liquid‐based cytology (LBC) was performed just before biopsy. We evaluated the specificity of the new oral cytodiagnostic criteria and the rates of change to OED and cancerization for each cytodiagnosis in leukoplakia and OLP. Results: One hundred and seventy patients were negative for intraepithelial lesion or malignancy (NILM), seven had low‐grade squamous intraepithelial lesions (LSILs), and two were indefinite for neoplasia (IFN). The specificity was 95% and the rates of OED change and cancerization in the observation period were 3.4% and 1.7%. In leukoplakia, there was a significant difference in the rates of change to OED and cancerization between negative for intraepithelial lesion or malignancy (NILM) and LSIL (odds ratio: 12.9; 95% CI: 1.72‐96.73). Conclusions: The new oral cytodiagnostic criteria have high specificity for oral mucosal lesions. And, it was suggested that the cases diagnosed with LSIL using new criteria have a high possibility of change to OED or cancerization in leukoplakia.